Optical properties and optoelectrical parameters of the quaternary chalcogenide amorphous Ge15SnxS35-xTe50 films - Sharma, Ishu; Sharma, Pankaj; Hassanien, Ahmed Saeed (Journal of non-crystalline solids, 2022)
•Novel six thermally evaporated a-Ge15SnxS35-xTe50, GSST, thin films were prepared.•Optical, dielectric, and linear and nonlinear properties and parameters have been studied.•Electronic polarizability, plasma frequency, covalence parameter, and others were discussed.•The value of dielectric constants and optical conductivity increase as Sn-percentage increases.•Addition of more Sn to the host matrix led to improve the optical and dielectric properties. This work is devoted to studying the optical properties of the novel thin a-Ge15SnxS35-xTe50, GSST, (x=0, 2, 4, 6, 8, 10 at.%) films of thickness 300 nm. Many dielectric characteristics, optoelectrical parameters, linear and nonlinear parameters of these films are investigated. Physical vapour deposition is used to fabricate these novel GSST films, at a constant rate of 10 nm/s in a vacuum of 10−5 mbar. X-ray diffractograms affirmed the amorphous nature of these GSST-films. Energy-dispersive X-ray analysis affirms that percentages of elements match those selected. Optical properties have been determined using UV-Vis-NIR-spectrophotometric transmission, T and reflection, R spectra in the range of 300 nm - 2500 nm. Optical constants are determined from T-and-R-spectra. The refractive index, n-values of films increase from 2.513 to 2.741 as Sn-content increases, while absorption index, k-values are in the range 10−2. The dielectric constant and optical conductivity increase as Sn-percentage increases. Electronic polarizability, plasma frequency, and covalence parameter are also discussed. Obtained results showed that GSST samples are suitable for use in many optical applications.